ANALYSIS OF LOCAL GOVERNMENT PERFORMANCE IN MANAGING DISTRIBUTION OF VILLAGE FUNDS (CASE STUDY IN KALIA VILLAGE, TALATAKO SUB-DISTRICT, TOJO UNA-UNA DISTRICT) - Riskawati, Riskawati; Amaliah, Tri Handayani; Lukum, Amir (Journal of Accounting and Business Education, 2016)
This research aims to find out the capacity of the Kalia Village in managing the allocated village budget and the factors that supports and inhibits the village apparatus in managing the budget. The research directly involves in this research. Descriptive qualitative method is used in this research with the qualitative approach. This research located in Kalia Village of Talatako sub-district, district of Tojo Una-Una. The data collected through direct observation, interview, and documentation. The informants in this research is 13 people, comprises of 5 village apparatus, 2 members of village facilitator and 3 community members. The data are analyzed interactively through data reduction, data display, and conclusion drawing or verification. It reveals tha the village apparatusâ capacity in managing the allocated village budget from planning, implementation, up to reporting and monitoring are less optimal. It is also found that majority of the village apparatus inadequate education level. In addition, the apparatus is also lacking in comprehending the tasks and functions of a village apparatus, as well as the technical skills of village apparatus hence the administrative requirements for allocated budget village are often submitted late that leads to late payment of allocated village budged.Keywords:Â Â  village government, village apparatus, management of allocated vilage budget